THE MAIN TRENDS IN THE DEVELOPMENT OF COMPLIANCE CONTROL IN THE BANKING ACTIVITY OF THE REPUBLIC OF KAZAKHSTAN (Journal of actual problems of jurisprudence, 2023)
The article discusses the main stages of the development of legislation on compliance control in the banking sector in the Republic of Kazakhstan. The analysis of the mechanism of state regulation of this institution, its organization, institutional interaction, functions and powers of second-tier banks, their relationship with the financial regulator is given. Proposals are being formulated to amend and supplement banking legislation. It contains an analysis of the latest regulatory changes in the field of banking compliance control.The banking system, being one of the important elements of the economy of any modern state, affects the vital activity of the society as a whole. The security and stability of the national currency, including its purchasing power and exchange rate against foreign currencies, depend on its condition. And that is why banking, as an integral part of the economy, should be one of the most dynamically developing sectors of the economy.Keywords: state, legal regulator, compliance control, regulator, Chinese walls, Astana International Financial Center.